2019
DOI: 10.7759/cureus.5014
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Reductase Polymorphism and Premature Coronary Artery Disease

Abstract: Methylenetetrahydrofolate reductase (MTHFR) catalyzes the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate, a co-substrate for homocysteine re-methylation to methionine. Its deficiency leads to an increased serum level of homocysteine, which is well-known to be associated with premature coronary artery disease (CAD). Our case demonstrates the association of MTHFR polymorphism with premature CAD and myocardial infarction (MI) despite normal homocysteine levels. Screening for MTHFR polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There are over 20 gene polymorphisms known for the MTHFR enzyme, where C677T is among the most studied ones. Although they are associated with different health issues, C677T is found to have the strongest association with CAD [6]. COVID-19 infection has been connected to prothrombotic conditions such as acute MI in patients, especially in the 1 st month of the primary infection [7], [8], [9] A recent study also demonstrated the longterm cardiovascular events post-COVID-19 infections, beyond the first 30 days after infection, building a cohort of 153,760 individuals with COVID-19 and comparing them to two sets of control cohorts.…”
Section: Introductionmentioning
confidence: 94%
“…There are over 20 gene polymorphisms known for the MTHFR enzyme, where C677T is among the most studied ones. Although they are associated with different health issues, C677T is found to have the strongest association with CAD [6]. COVID-19 infection has been connected to prothrombotic conditions such as acute MI in patients, especially in the 1 st month of the primary infection [7], [8], [9] A recent study also demonstrated the longterm cardiovascular events post-COVID-19 infections, beyond the first 30 days after infection, building a cohort of 153,760 individuals with COVID-19 and comparing them to two sets of control cohorts.…”
Section: Introductionmentioning
confidence: 94%
“…Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme of homocysteine metabolism, providing a methyl group for Hcy remethylation into methionine and maintaining the normal levels of Hcy in the body [ 11 ]. Mutations of the MTHFR gene decrease MTHFR enzyme activity that prevents Hcy remethylation and increases Hcy levels in plasma [ 11 , 12 ]. The MTHFR gene has at least two functional polymorphisms, 677T and 1298C.…”
Section: Introductionmentioning
confidence: 99%
“…16 The most common mutated form of MTHFR is C677T, whereas the mutant allele TT can increase the probability of a high Hcy level. [17][18][19] The previous studies have been done for detecting the association of Hcy enzyme gene polymorphisms and CHD with contradictory results. [20][21][22] Moreover, scanty reports are available from the Indian scenario as the majority of studies from Asia are confined to China, Japan, and the Sri Lankan population.…”
Section: Introductionmentioning
confidence: 99%